A Relationship Framework for Building Information Modeling (BIM) Capability in Quantity Surveying Practice and Project Performance - Wong, P.F.; Salleh, H.; Mohd-Rahim, F.A. (Consejo Superior de Investigaciones Científicas, 2015)
Construction industry has suffered from poor project performance and it's crucial to find out solution to improve this issue. Quantity surveyors (QSs) play a key role in managing project cost. However, their method of performing tasks is tedious till affect the project performance. Building information modeling (BIM) application is attaining attention in the construction industry as a mean to improve the project performance. However, the adoption is low among QSs due to limited study of the BIM's capabilities in their profession. This research aims to identify the BIM capabilities in quantity surveying practices and examine its relationship with project performance by developing a relationship framework. Data were collected through questionnaire survey and interview in Malaysia. Questionnaire results revealed that several BIM capabilities were significantly correlated with project performance and they were validated through interview. The relationship framework will guide QSs to focus on the identified BIM capabilities for better project outcomes.